Comparative Genomics of Potato Common Scab-Causing Streptomyces spp. Displaying Varying Virulence - Hudec, Cindy; Biessy, Adrien; Novinscak, Amy; St-Onge, Renée; Lamarre, Simon; Blom, Jochen; Filion, Martin (Frontiers in Microbiology, 2021)
Common scab of potato causes important economic losses worldwide following the development of necrotic lesions on tubers. In this study, the genomes of 14 prevalent scab-causing Streptomyces spp. isolated from Prince Edward Island, one of the most important Canadian potato production areas, were sequenced and annotated. Their phylogenomic affiliation was determined, their pan-genome was characterized, and pathogenic determinants involved in their virulence, ranging from weak to aggressive, were compared. 13 out of 14 strains clustered with S. scabiei, while the last strain clustered with S. acidiscabies. The toxicogenic and colonization genomic regions were compared, and while some atypical gene organizations were observed, no clear correlation with virulence was observed. The production of the phytotoxin thaxtomin A was also quantified and again, contrary to previous reports in the literature, no clear correlation was found between the amount of thaxtomin A secreted, and the virulence observed. Although no significant differences were observed when comparing the presence/absence of the main virulence factors among the strains of S. scabiei, a distinct profile was observed for S. acidiscabies. Several mutations predicted to affect the functionality of some virulence factors were identified, including one in the bldA gene that correlates with the absence of thaxtomin A production despite the presence of the corresponding biosynthetic gene cluster in S. scabiei LBUM 1485. These novel findings obtained using a large number of scab-causing Streptomyces strains are challenging some assumptions made so far on Streptomyces’ virulence and suggest that other factors, yet to be characterized, are also key contributors.